Tweeting and Eating: The Effect of Links and Likes on Food-Hypersensitive Consumers’ Perceptions of Tweets - Hamshaw, Richard J. T.; Barnett, Julie; Lucas, Jane S. (Frontiers in Public Health, 2018)
Moving on from literature that focuses on how consumers use social media and the benefits of organisations utilising platforms for health and risk communication, this study explores how specific characteristics of tweets affect the way in which they are perceived. An online survey with 251 participants with self-reported food hypersensitivity took part in an online experiment to consider the impact of tweet characteristics on perceptions of source credibility, message credibility, persuasiveness and intention to act upon the presented information. Positioning the research hypotheses within the framework of the Elaboration Likelihood Model and Uses and Gratifications Theory the study explored motivations for using social media, and tested the impact of the affordances of Twitter – 1) the inclusion of links and 2) number of social validation indicators (likes and retweets). Having links accompanying tweets significantly increased ratings of the tweets’ message credibility, as well as persuasiveness of their content. Socially validated tweets had no effect on these same variables. Parents of food hypersensitive children were found to utilise social media for social reasons more than hypersensitive adults; concern level surrounding a reaction did not appear to alter level of use. Links were considered valuable in getting social media users to attend to useful or essential food health and risk information. Future research in this area can usefully consider the nature and the effects of social validation in relation to other social media platforms and with other groups.